Edward Prendick’s Harrowing Journey on Doctor Moreau’s Island: A Tale of Trauma in H.G. Wells’ Novel - Tangkilisan, Sesar; Husain, Dahlia; Mariana, Ana; Otoluwa, Moon Hidayati; Rosida, Ana (Institut Agama Islam Negeri (IAIN) Manado, 2024)
This study explores the representation of traumatic experiences in H.G. Wells' novel The Island of Doctor Moreau. Traumatic experiences are unpredictable, unpreventable situations that overwhelm victims and disrupt their ability to cope. Literature can provide insights into the range of responses to such overwhelming experiences as a reflection of human existence. The objective of this research is to increase awareness and understanding of trauma and mental illness through the analysis of literary depictions. Using a qualitative research approach, the study examines the traumatic experiences encountered by the protagonist, Edward Prendick, in the novel. The analysis categorizes Prendick's traumatic experiences into three main themes: a) being stranded, drifting away, and lost; b) witnessing death and seeing dead bodies; and c) meeting scary creatures, being attacked, and being terrorized. The findings reveal how the novel portrays the psychological and emotional impact of trauma on the protagonist, highlighting the challenges faced by victims of overwhelming and life-threatening situations. By analyzing the literary representation of trauma, this study aims to foster greater empathy and understanding for those affected by traumatic experiences and mental health issues. The in-depth qualitative analysis of the narrative techniques and thematic elements in the novel contributes to the literature on the literary depiction of trauma and its implications for raising awareness and promoting mental health.Keywords: Traumatic experiences, psychology, novel